Criminological Study of the Influence of Social Media on Cyberbullying Crimes in Indonesia - Aditya Restu Hapriyanto; Bintara Sura Priambada; Aris Setyo Nugroho (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2026)
The rapid advancement of digital technology has transformed patterns of human interaction, particularly through social media, which has become an integral part of everyday life. In Indonesia, social media usage is remarkably high, with teenagers representing one of the largest and most active user groups. Although social media provides various benefits such as communication, entertainment, and self-expression, it also facilitates negative behaviors, including cyberbullying. Cyberbullying refers to repeated acts of intimidation, humiliation, or harassment conducted through digital platforms with the intent to cause psychological harm. This study employs normative legal research methods with a criminological approach to analyze the influence of social media on cyberbullying in Indonesia. From a criminological perspective, cyberbullying is associated with factors such as anonymity, peer influence, weak social control, and the viral nature of digital interactions, which encourage deviant behavior in cyberspace. The legal framework in Indonesia, particularly the Electronic Information and Transactions Law (UU ITE) and of the Law of the Republic of Indonesia Number 1 of 2023 on the Penal Code (KUHP), provides the basis for criminal liability for cyberbullying perpetrators. However, law enforcement faces significant challenges due to the dynamic and borderless characteristics of cyberspace. This study contributes to understanding social media as a catalyst for cyberbullying and emphasizes the importance of criminological theory in addressing its root causes. Furthermore, it highlights the urgency of comprehensive preventive measures, including legal reform, digital education, and strengthened parental supervision, to reduce the risks and impacts of cyberbullying among Indonesian youth.